Reorganization of Postural Stability After Tram Flap Breast Reconstruction Surgery: A Longitudinal Case Report. Issue 3 (July 2019) - Bussey, Melanie D.; Aldabe, Daniela; Jones, Lynnette M.
Abstract : Background Context: Transverse rectus abdominis myocutaneous (TRAM) flap breast reconstruction is a common method of reconstruction performed after mastectomy. However, the short and long-term effect on posture, balance, and coordination is unknown. Purpose: The purpose of this study was to investigate the effects of TRAM flap breast reconstruction on anticipatory postural control and balance in a breast cancer survivor. Study Design: A repeated-measures cohort design. Patient Sample: A 47-year-old woman who underwent ipsilateral mastectomy and TRAM flap breast reconstruction. Outcome Measure: Anticipatory muscle activity including muscle onset timing, magnitude of muscle activation, and center-of-pressure displacement during a modified Trendelenburg task. Muscle onsets occurring before initiation of weight shift were considered "early activation" and likely to represent a feedforward postural control mechanism whereas muscle onsets occurring after weight shift were considered "late activation" representing reliance on feedback mechanism for postural control. Methods: Electromyographic muscle activity and displacement of center of pressure were examined in a single-subject design with pre- and post-TRAM flap surgery measures taken 6 days preoperation, 6 weeks, and 13 weeks postoperation. Results: The timing of muscle onset differed significantly day-to-day for all muscles. Preoperatively, the unaffected side presented earlier activation compared with the affected side. At 6 weeks, there were no early activations. At 13 weeks, early activation was identified in 6 of 8 muscles. Reaction time and balance instability were significantly greater at 6 weeks and highest on the affected. Conclusions: The permanent disruption of the rectus abdominis had an immediate and significant impact on muscle activity and balance, which was restored by 13 weeks postoperation without specifically targeted stability rehabilitation.